Development of a reference database for ion beam analysis : report of a coordinated research project on reference database for ion beam analysis. (IAEA-TECDOC, 2015)
"Ion beam analysis techniques are non-destructive analytical techniques used to identify the composition and provide elemental depth profiles in surface layers of materials. The applications of such techniques are diverse and include environmental control, cultural heritage and conservation and fusion technologies. Their reliability and accuracy depends strongly on our knowledge of the nuclear reaction cross sections, and this publication describes the coordinated effort to measure, compile and evaluate cross section data relevant to these techniques and make these data available to the user community through a comprehensive online database. It includes detailed assessments of experimental cross sections as well as attempts to benchmark these data against appropriate integral measurements."--Publisher's description.